AUGMENTATION OF BIOLOGICAL TITER OF FOOT AND MOUTH DISEASE VIRUS IN IN VITRO CULTURE - Q. Akram; K. Muhammad; M. Rabbani; J. Nazir; M. Nawaz; K. Hanif; Z. Shakoor (Journal of Animal and Plant Sciences, 2013)
Foot and Mouth Disease (FMD) virus grew well on BHK-21 cell line. The virus showed poor tissue culture infective dose 50 (TCID50) that was log 103.2±0.2 in BHK-21 cell line having Glasgow Minimal Essential Medium (GMEM) without Fetal Calf Serum (FCS). Addition of one per cent FCS in the medium @ one percent increased log 107.1±0.2 units of virus TCID50. Incubation temperature of 350 C and 370 C supported the multiplication and maintenance of BHK-21 cells and yielded log106.6±0.1 and log107.0±0.2units of virus TCID50, respectively. Each serotype of FMD virus showed log106.29±0.07 units of virus TCID50 in the stationary monolayer of BHK-21 cells in roux flask (75cm 2), log107.66± 0.02 units of virus TCID50 in roller bottles (490cm2) and log108.34 ± 0.07 units of virus TCID50 on 0.2 g of micro-carriers suspending in 200 ml of the growth medium in stirring bottle. The infectivity titer/TCID50 of each of the virus serotypes was significantly higher in roller bottles than that achieved in roux flasks (p<0.05) and was significantly higher in stirring bottle containing micro-carriers suspending in the growth medium than that of harvested in roller bottle (p<0.05). It is concluded that the infectivity titer of the virus is directly proportional to number of BHK-21 cells in the culture system.
Keywords: Anchorage dependant BHK-21 cells; roller bottles; infectivity titer; FMD virus